Agency is an illusion: Barriers to participation in teacher education and schools - Magerøy, Solveig Maria (Nordic Journal of Comparative and International Education (NJCIE), 2022)
This article investigates student teachers’ perceptions and experiences in teacher education regarding codetermination and participation as a part of education for democracy and citizenship, along with how they visualize their future teaching in this interdisciplinary theme as teachers in schools. The data material includes 16 extensive interviews with six student teachers in their final year of teacher education in Norway. The results demonstrate a discrepancy between their perceptions and praxis concerning participation. First, the student teachers in their last year of teacher education felt the ability to participate in and through their education was present, but they chose not to take advantage of this possibility. They underlined the importance of participation and agency in education for democracy but did not seem to assign the same importance to their involvement in education. Second, when visualizing how to teach democracy and citizenship in schools, they suggested facilitating pupils’ self-determination in situations where the pupils’ decisions and participation do not change or impact anything. In so doing, they described participation and agency as an illusion; something that is important, necessary, and valuable but with no practical implications. The student teachers seemed to transfer this same illusion of pupils’ agency and participation in their planned teaching in the future.